Research Papers : The relationship between allelic variations of Vrn-1 and Ppd-1 and agronomic traits in Korean wheat cultivars - Cho, Eun Jin; Kang, Chon-Sik; Yoon, Young Mi; Park, Chul Soo (The Indian Journal of Genetics and Plant Breeding, 2016)
The allelic variations at the Vrn-1 and Ppd-1 loci of Korean wheat cultivars were determined to evaluate their effects on agronomic traits and response to vernalization treatment. Korean wheat cultivars displayed high frequency of Vrn-D1a and Ppd-B1b alleles, but all of the tested cultivars carried vrn-A1, vrn-B1, Ppd-A1b and Ppd-D1a alleles at the corresponding loci. Regardless of vernalization treatments, Korean wheat cultivars carrying the vrn-D1 allele showed longer days to flag leaf unfolding than those with the VrnD1a allele. Unvernalized cultivars carrying the vrn-D1 allele also exhibited larger final leaf number than those with the Vrn-D1a allele. However, there were no significant differences in the response of the Korean wheat cultivars to vernalization treatment based on allelic variation at the Ppd-1 loci. With respect to agronomic traits, the Vrn-D1a allele was related to increased grain yield and decreased thousand kernel weight compared to the vrn-D1 allele. Cultivars carrying both Vrn-D1a and Ppd-B1b alleles produced higher grain yield (5.5 tons/ha) than those with the vrn-D1 and Ppd-B1b alleles (5.0 tons/ha)